Analysis of the polyphosphate-accumulating microflora in phosphorus-eliminating, anaerobic-aerobic activated sludge systems by using diaminopropane as a biomarker for rapid estimation of Acinetobacter spp. - Auling, G (1991)
Polyphosphate-accumulating gram-negative bacteria were isolated from different anaerobic-aerobic activated sludge systems with diverse processes for enhanced biological phosphorus (P) elimination. Of 22 isolates, 10 were allocated to the genus Acinetobacter by using multiple-test systems and soluble protein and polyamine patterns. As diaminopropane (DAP) appears to be the characteristic main polyamine compound produced by Acinetobacter spp., it was used as a biomarker for the genus. The high DAP contents of representative samples from municipal wastes with enhanced biological P elimination indicated that Acinetobacter spp. can be dominant organisms in sewage treatment plants with low organic loading and nitrification and denitrification steps. Contrary to accepted opinion, sludge from treatment plants with efficient P removal and high organic loading had a low DAP content, indicating that bacteria other than Acinetobacter spp. are responsible for enhanced biological P elimination in these plants.